Ketahanan Hidup Sel Acetobacter xylinum pada Pengawetan secara Kering-Beku Menggunakan Medium Pembawa (Viability of A. xylinum Subjected to Freeze Drying Using Carrier Media) - Dewi, Pramesti (Biosaintifika: Journal of Biology & Biology Education, 2009)
A research on the use of sucrose and lactose as carrier media to protect Acetobacter xylinum cell subjected to freeze drying has been done. The aim of the research was to know the number of the viable cells from dried culture and to know the concentration of the carrier medium that would give best result. The best result is sucrose at the concentration of 15% that produced 28.2 x 106 viable cells/ ml of rehidrated culture. The rehidrated culture used in the research was Schramm & Herstin medium.